Scent Pecco Aroma From Colonial Heritage of Dutch East Indies Became Excellence Tour in Kerinci District 1933-1945 - Nengsi; Siti Fatimah; Buckhari Nurdin (Fakultas Ilmu Pendidikan UNP)
Before independence in 1933 scent pecco is a lake that is a kind of water body in a plantation tea having a garden be resting place after the dutch colonial gardening and after kemerdekan this place in made tourism kerinci in the district .The work is aiming to express history scent pecco originating from the netherlands became tourist colonial superior kerinci district and the kind of research it includes historical research the method of a heuristic , criticism of , interpretation and historiografi .The result showed that tourism scent pecco but is a lake having a gorge berpanorama beautiful and natural beauty of being in a stretch of tea tengan-tengah plantation exactly under the mountain kerinci is also a historic tourism .Conclusions scent pecco is the result of a relic colonial dutch indies and current to tourism district in seed kerinci appointed for a holiday